Enhancing Squalene Production in Saccharomyces cerevisiae by Metabolic Engineering and Random Mutagenesis - Xia, Lu; Lv, Yunbin; Liu, Song; Yu, Shiqin; Zeng, Weizhu; Zhou, Jingwen (Frontiers in Chemical Engineering, 2022)
Squalene is an important polyunsaturated triterpene with wide applications in the food, cosmetics, and pharmaceutical industries. Currently, the main method for squalene production is extraction from oil-producing plants, but the scale is limited. The microbial fermentation with Saccharomyces cerevisiae still needs improvement to be economically viable. This study aimed to improve squalene production by metabolic engineering and random mutagenesis. First, the mevalonate (MVA) pathway was enhanced, by integrating tHMG1 and IDI1 into multi-copy site Ty2. Subsequently, the ACL gene from Yarrowia lipolytica, encoding citrate lyase was introduced and the β-oxidation pathway was enhanced with multiple copies of key genes. In addition, a high throughput screening strategy based on Nile red staining was established for high squalene-producer screening. After treatment with ARTP mutagenesis, a higher-producing mutant was obtained, with squalene production enhanced by 18.4%. A two-stage fermentation of this mutant in a 5L bioreactor produced 8.2 g/L of squalene. These findings may facilitate the development of industrial squalene production by fermentation and potentially, other terpenoids.